Systematic Literature Review: Hospitality And Tourism 5.0: Enhancing Sustainable Tourism Experiences In The Digital Era - Kezia Mathilda Ruth Kappu; Evi Novianti; Priyo Subekti; Awaludin Nugraha (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
The rapid development of digital technologies has accelerated the transformation of the tourism and hospitality industry toward the Hospitality and Tourism 5.0 paradigm, which emphasizes the integration of intelligent technologies with a human-centered approach and sustainability principles. This study aims to systematically review the development of Hospitality and Tourism 5.0 in academic literature and examine its role in creating sustainable tourism experiences in the digital era. This research employs a Systematic Literature Review (SLR) following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Literature was collected from Scopus, Web of Science, Google Scholar, and Garuda databases, covering publications from 2014 to 2024. The initial search identified 120 articles, which were screened through identification, screening, eligibility, and inclusion stages, resulting in 25 articles selected for further analysis. The findings reveal that digital technologies such as artificial intelligence, big data, the Internet of Things, and smart tourism systems play a significant role in enhancing service personalization, operational efficiency, and tourism experience quality. Moreover, Hospitality and Tourism 5.0 supports sustainable tourism through improved resource management, reduced environmental impacts, and greater local community engagement. However, challenges related to human resource readiness, digital inequality, and data ethics remain significant barriers to its implementation.